IIVR, Varanasi —the harbinger of vegetable revolution - Dutt, Som (Indian Horticulture, 2019)
India is blessed with diverse agroclimatic conditions, and more than 90 vegetables are grown. Tomato, brinjal, chilli, vegetable pea, French bean, cowpea, dolichos bean, cauliflower, cabbage, carrot, radish, beet-root, spinach, amaranthus and moringa are important. Besides, bitter gourd, pumpkin, pointed gourd, watermelon, muskmelon, bottle gourd, sponge gourd, ridge gourd, cucumber, ash gourd, broccoli, summer squash, tinda, chow-chow, drumstick, basella, curry leaf, lettuce, etc. are also gaining momentum due to their nutritional and export potential. The IIVR Varanasi, has contributed remarkably in vegetable production, providing nutritional security in our country.